Public Perception of Islamic Higher Education Institutions on Twitter in Indonesia: A Social Media Sentiment Analysis - Nikmah, Rofingatun; Rasyid, Erwin (CHANNEL: Jurnal Komunikasi, 2023)
With the advent of social media, particularly Twitter, public opinion has become a dynamic and influential force. This study explores the public's perception of Islamic higher education institutions on Twitter, employing sentiment analysis to decipher the nuances of public sentiment. A comprehensive quantitative research methodology employing sentiment analysis was applied to a dataset of 11,809 tweets collected from 2018 to 2022, all focused on perceptions of Islamic higher education. The preprocessing phase involved cleaning, case folding, punctuation, number removal, stopword elimination, and tokenization. Sentiment analysis techniques were utilized to categorize tweets into positive, negative, or neutral sentiments. The analysis revealed a prevalent positive sentiment, constituting 73.16% of the dataset, 21.37% exhibited negative sentiment, and 5.47% reflected neutral sentiment. Visualizations, including word clouds, highlighted key topics shaping public perception. Words like "university," "religion," and "student" emerged prominently, influencing sentiment across categories. These results underscore a positive public perception of Islamic higher education, indicating the effectiveness of social media in shaping favorable opinions. The research emphasizes the significance of social media, specifically Twitter, as a platform for fostering positive perceptions of Islamic higher education. Strategic communication, proactive content dissemination, and responsive engagement are essential for enhancing institutional image. Future research directions, including advanced methodologies like topic modeling and word association techniques, promise a deeper understanding of public sentiment nuances, guiding educational institutions and policymakers toward effective social media engagement strategies